Treatment of high risk symptomatic intracranial atherosclerosis with balloon mounted coronary stents and Wingspan stents: single center experience over a 10 year period. (28th July 2011) - Tarlov, Nicholas; Jahan, Reza; Saver, Jeffrey L; Sayre, James W; Ali, Latisha K; Kim, Doojin; Duckwiler, Gary R; Tateshima, Satoshi; Viñuela, Fernando; Liebeskind, David S
Abstract : Background: Stenting of symptomatic intracranial atherosclerosis remains under investigation, yet this option to potentially avert subsequent stroke has been offered at select centers under humanitarian device exemption and off-label use for several years. Methods: Retrospective case series of consecutive patients undergoing stenting with Wingspan and balloon mounted coronary stents for symptomatic intracranial atherosclerosis at a single institution. Recurrent symptomatic ischemia in the territory of the stented artery was ascertained. Rates of recurrent ischemic stroke were calculated per patient-year of follow-up and were compared with medically treated patients in the Warfarin–Aspirin Symptomatic Intracranial Disease (WASID) trial. Results: During the 10 year study period, 41 cases of intracranial stenting were identified. Stenoses were severe (>70%) in 88% of patients. Stenting procedures occurred a median of 14 days from the most recent symptomatic event. 19 Wingspan stents and 22 balloon mounted coronary stents were deployed. Four strokes occurred within 24 h of stenting, seven within 1 month and eight within 3 months. By 3 months after stenting, no further strokes occurred during up to 2 years of follow-up. Patients had 0.194 ischemic strokes per person-year of follow-up, compared with 0.083 ischemic strokes per person-year of follow-up in the aspirin arm of WASID and 0.065 ischemic strokes per person-year of follow-up in the warfarin arm of WASID. Conclusions: Stenting of symptomatic intracranial atherosclerosis in a high risk subset of cases with advanced degree of luminal stenosis may be associated with an increased early risk of recurrent ischemic stroke.